Effectiveness of Regional Human Rights Adjudication: ECHR/IACtHR Evidence and Implications for Asia - Kim, Ryan Minhyuk (Technium Social Sciences Journal, 2025)
The research investigates international human rights compliance through legal frameworks and institutional changes by studying three regions of Europe and the Americas and Asia. The research evaluates ECHR and IACtHR through structured case studies to demonstrate how their binding treaties and individual access and enforcement systems differ from ASEAN and SAARC’s non-judicial frameworks with weak structures. The study uses Dudgeon v. UK and Barrios Altos v. Peru to demonstrate how court-ordered decisions and monitoring systems and government backing determine the level of implementation. The research identifies three essential elements which determine effectiveness: (1) legally enforceable documents that require or accept court jurisdiction and (2) effective enforcement systems with follow-up procedures and (3) enduring political backing from civil society organizations. The European region achieves high compliance rates because of its extensive institutional framework yet the Americas show variable results in their human rights impact. The region of Asia faces obstacles to court establishment because of its non-interference principles and political divisions and absence of enforceable legal frameworks. The research supports a step-by-step approach to policy implementation which includes creating binding subregional agreements and strengthening AICHR/SAARC authority and testing judicial panels and developing compliance standards through NHRI-NGO partnerships and UN system support.